Iranian postgraduate students’ beliefs about English language learning / Zoiemiow Vakili - Vakili, Zoiemiow (2013)
Beliefs are “general assumptions that students hold about themselves as learners, about factors influencing language learning, and about the nature of language learning and teaching” (Victori & Lockhart 1995, P.224).Language learners’ beliefs lead their actions, particularly in the process of learning. Learners’ beliefs can help teachers to have a better understanding of the learners’ learning process and their success in classrooms. According to Horwitz (1988), “ knowledge of students’ beliefs about language learning may provide teachers of languages with a better understanding of their students’ expectations of, commitment to, success in and satisfactions with language classes” ( Horwitz, 1988 : 283). Although, there have been many studies on the notion of beliefs about language learning so far, yet very few of them explored Iranian students’ beliefs about English language learning. In an attempt to fill this gap, this research was conducted to find out: 1) What are Iranian postgraduate students’ beliefs about English language learning? 2) Is there any shift in their beliefs after attending English classes? 3) What is the role of gender on their beliefs about language learning? In order to achieve the objectives of the research and to answers to the above research questions, this study employed Horwitz’s model (Beliefs About Language Learning Inventory, BALLI 1988). BALLI is based on the normative approach and it is used to investigate Iranian postgraduate students’ beliefs about English language learning at the University of Malaya (UM) in Kuala Lumpur, Malaysia. Data was collected from 30 Iranian students, 15 males and 15, females at two different periods of time through distributing a modified 34-items questionnaire based on Horwitz’s BALLI (1988). The Pre-test data was collected at the beginning of the compulsory English course/s for the participants and the post- test data was gathered at the end of the same classes in order to find out whether there was a shift in their beliefs about English language learning after a period of one semester of instructions or not. The BALLI in this study measured students’ beliefs about learning English in five main categories namely: 1) Difficulty of Language Learning, 2) Foreign Language Learning, 3) The Nature of Language Learning, 4) Learning and Communication Strategies and 5) Motivation and Expectations. Moreover, a semistructured interview based on the BALLI’s items was done in order to get more information and insights about the respondents’ beliefs about English language learning. Through a descriptive analysis and a statistical analysis (by using SPSS version 16) the findings of this study show that Iranian postgraduate students in UM held a variety of beliefs about learning English. The results of t-test indicate there was not much difference in their beliefs before attending the English classes and after being instructed for a period of one semester. In terms of gender, both male and female students held firm beliefs about learning English and the only significant shift in their beliefs was related to the males’ beliefs about English language learning in the “Foreign Language Aptitude” category. The findings enhance our understanding of how exploring learners’ beliefs can guide us to better meet learners’ needs, expectation and their aims in the process of English language learning.